4-(4-Chlorophenyl)-8-methyl-2-oxo-1,2,5,6,7,8-hexahydroquinoline-3-carbonitrile - Asiri, Abdullah M. (International Union of Crystallography, 2011)
The six-membered N-heterocyclic ring of the title compound, C(17)H(15)ClN(2)O, is fused with a methyl-substituted cyclohexene ring. The approximately planar nitrogen-bearing ring (r.m.s. deviation 0.019 Å) is aromatic, and the N atom shows a trigonal–planar coordination; its benzene substituent is aligned at 77.1 (1) °. The cyclohexene ring adopts a half-chair conformation. In the crystal, inversion-related molecules are linked by pairs of N—H⋯O hydrogen bonds, generating dimers.